Moderation at Local Level: How Does Post-Islamism Elite Become More Moderate? - Djafar, Alamsyah Muhammad; Tsauro, Ahalla (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2023)
The explanation of when and under what conditions post-Islamism elite is more moderate toward democratic values is still up for debate. The majority of studies explain these issues at the national level without taking into account the local dynamics and variety of experiences. Based on a comparative study on Partai Keadilan Sejahtera (Prosperous Justice Party or PKS) at the local level (Depok and Sukabumi City, West Java) on the acceptance and repudiation of religious freedom rights, this study argues that moderation is not a linear process and is largely determined by strategic confidence, where the moderation can maintain or even expand their power and influence. This study demonstrates how social pressure, organizational structure, and political experience are interconnected and influence the choice of moderation or immoderation.